How to recognize national lands (natural resources) and exceptions (non-national resources): objection methods and authoritie - Bineshian, Arash (DIXI, 2023)
The principles of natural resources include recognition, governance, protection, and exploitation of natural resources, among which recognition is the most important. Any enforcement of sovereignty over national lands requires the implementation of a legal recognition process. So, recognizing national lands and exceptions is of great importance. In other words, recognizing national lands and exceptions is the first step in protecting these lands and preventing their waste and change of use. Each country’s natural resources and environment do not belong only to it, but to all the people of the world. In this way, the destruction of national lands does not only mean the deterioration of a part of that country’s capital, but also the destruction of a part of the natural resources and environment of the planet and the wealth of the whole world. Unfortunately, most developing countries have a full-scale war against natural resources and the environment. The author is concerned not only about the preservation of natural resources and the environment in Iran, but also about the whole world. Governments should be forced to preserve, restore and develop natural resources and the environment by using practical international tools, and there is no other choice but to force.